2011
DOI: 10.1037/a0021362
|View full text |Cite
|
Sign up to set email alerts
|

A genetically informed study of associations between family functioning and child psychosocial adjustment.

Abstract: Research has documented associations between family functioning and offspring psychosocial adjustment, but questions remain regarding whether these associations are partly due to confounding genetic factors and other environmental factors. The current study used a genetically informed approach, the Children of Twins design, to explore the associations between family functioning (family conflict, marital quality, and agreement about parenting) and offspring psychopathology. Participants were 867 twin pairs (388… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 105 publications
(152 reference statements)
1
22
0
1
Order By: Relevance
“…Such results are clearly consistent with recent work using a Children-of-Twins design (Harden et al, 2007; Schermerhorn et al, 2011) as well as past work pointing toward gene-environment correlation as a potential mechanism underlying the relationship between conflict and child adjustment problems (Feinberg et al, 2005; Horwitz et al, 2010; Neiderhiser et al, 1999). Furthermore, because the CPIC provides multiple dimensions of inter-parental conflict from the child’s perspective, specificity in these relationships could also be determined (e.g.., rGE involving threat and internalizing problems and rGE involving self-blame and externalizing problems).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such results are clearly consistent with recent work using a Children-of-Twins design (Harden et al, 2007; Schermerhorn et al, 2011) as well as past work pointing toward gene-environment correlation as a potential mechanism underlying the relationship between conflict and child adjustment problems (Feinberg et al, 2005; Horwitz et al, 2010; Neiderhiser et al, 1999). Furthermore, because the CPIC provides multiple dimensions of inter-parental conflict from the child’s perspective, specificity in these relationships could also be determined (e.g.., rGE involving threat and internalizing problems and rGE involving self-blame and externalizing problems).…”
Section: Discussionsupporting
confidence: 91%
“…The Children-of-Twins design, for example, assesses adult twins (with their own families), and thus obtains individual-level report of marital relationships. Research using this more recent design has demonstrated that the relationship between family factors, including marital quality and child adjustment appears to be, in part, genetically-mediated (Schermerhorn et al, 2011). These findings offer further support of shared etiological processes (i.e., potential gene-environment correlations).…”
mentioning
confidence: 99%
“…Results coupled with a recent publication from TOSS (Schermerhorn et al, 2010) also enhance our understanding of family dynamics. Schermerhorn et al (2010) revealed that marital quality is linked to child problem behaviors through genetic and environmental pathways, whereas family conflict is linked to child behavior problems family conflict entirely through environmental pathways. The genetic pathway linking marital quality to child problem behaviors suggest that parents’ heritable characteristics influencing marital quality are also transmitted to the child and are expressed as problem behaviors.…”
Section: Discussionmentioning
confidence: 66%
“…In absence of specific information on the reasons for discrepancy between mother- and child-reports, we consider this a sensible approach. Moreover, relying exclusively on children’s evaluation of family conflict has been shown to increase the confounding effect of genetic factors (Schermerhorn et al, 2011). Before computing composite measures, we imputed missing cases with stochastic regression in SPSS; random error was modeled with regression residuals (see Allison, 2002).…”
Section: Methodsmentioning
confidence: 99%